The Impact of Covid-19 on Financial Institutions (Banks) - Samim, Nargis (Journal of Social Sciences - Kabul University, 2022)
Corona virus is a challenge that has caused health, social and economic problems all over the world. Due to the spread of this virus, the economic activities of businesses were closed in a large number of countries and created an economic recession in the majority of countries. In addition, the banking industry, like other sectors, was affected by the spread of the corona virus, and banks were forced to adopt new policies to reduce the effects of this virus. Uncertainty caused by the corona virus has systematically exposed banks to a variety of risks such as: loan risk, market risk, liquidity risk, operational risk and other banking risks. In Afghanistan also, the quarantine and holidays by the corona virus caused a decrease in bank transactions, an increase in operational costs, a decrease in bank income and a decrease in bank profitability.